Symptomatic hepatitis secondary to disseminated coccidioidomycosis in an immunocompetent patient. (15th April 2014) - Kuprian, Mikhail; Schofield, Christina; Bennett, Steven
Abstract : A young man from California presented with acute onset of cough, fevers, night sweats and pruritus with dark urine. Laboratory studies were notable for moderate transaminitis with elevated bilirubin and eosinophilia. Hepatitis panel, HIV screen and heterophile antibodies were negative. CT scan showed multiple bilateral focal opacities with hilar and mediastinal lymphadenopathy with no ductal dilation or gallbladder stones. The patient had positive coccidioidomycosis serologies and he was started on fluconazole with resolution of symptoms and improvement in transaminitis over the next month. This article highlights a rare manifestation of disseminated coccidioidomycosis with symptomatic hepatitis. Although an increasingly prevalent infection found in southwest USA, dissemination is rare in immunocompetent hosts. Postmortem studies suggest hepatic involvement is common in disseminated infection. However symptomatic hepatitis is rare, with only three cases of symptomatic hepatitis found in the literature.